Media views in Indonesia on the belt and road initiative policy : a study of Indonesian new media reports to the BRI project of China in Indonesia - Anang Masduki; Liu Jian; Panqiang Niu (International Journal of Communication and Society, 2023)
The pros and cons of the project of BRI in Indonesia cannot be separated from mainstream and online mass media coverage in Indonesia. In the coverage, there is a framing to build a story so that the influence of journalists is so great that the news is read by the public. In addition, the informant factor as well as ideology influence the news statements that appeared in the media. This research focuses on how the construction of the mass media coverage in Indonesia, especially the new media (online news) related to the cooperation between Indonesian and Chinese government in the BRI project. The research uses a qualitative descriptive approach and framing analysis. The research object is the official portal of online news such as Media Indonesia.com. Republika.com Kompas.com, and Jawapos.com. Based on the results of research and discussion, it can be concluded that the framing of online media coverage Kompas.com, mediaindonesia.com, jawapos.com and Republika.com have differences. Kompas.com and jawapos.com put more emphasis on scientific and intellectual language because both of their readers have a better level of education and economics. Whereas republika.com and mediaindonesia.com tend to use straightforward and simple language. Kompas.com and jawapos.com lead opinions to think critically with data while republika.com and mediaindonesia.com leads the public to see the implementation of Indonesia's and China economic cooperation programs in the BRI project.